2016
DOI: 10.1097/ccm.0000000000001380
|View full text |Cite
|
Sign up to set email alerts
|

A Selective V1A Receptor Agonist, Selepressin, Is Superior to Arginine Vasopressin and to Norepinephrine in Ovine Septic Shock*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…One of several approaches being investigated to address oedema and endothelial injury is the use of selepressin, a selective vasopressin type 1a receptor agonist that increases arterial pressure and has the potential to reduce vascular leakage and pulmonary oedema. Preclinical studies in an ovine model of septic shock showed clear survival benefits of selepressin over vasopressin and noradrenaline, especially when administered early 121 .…”
Section: Managementmentioning
confidence: 99%
“…One of several approaches being investigated to address oedema and endothelial injury is the use of selepressin, a selective vasopressin type 1a receptor agonist that increases arterial pressure and has the potential to reduce vascular leakage and pulmonary oedema. Preclinical studies in an ovine model of septic shock showed clear survival benefits of selepressin over vasopressin and noradrenaline, especially when administered early 121 .…”
Section: Managementmentioning
confidence: 99%
“…Arginine vasopressin administration only has been recommended to treat refractory shock in intensive care units. 56 …”
Section: Is This Issue Adequately Addressed In Available Data?mentioning
confidence: 99%
“…What do we learn from the study by He et al (17)? Clearly, this study is the logical extension of the above-mentioned previous article by Maybauer et al (16), and it elegantly confirms these authors' conclusion that selepressin indeed compares favorably with AVP and the clinical standard vasopressor norepinephrine with respect to plasma leakage into the extravascular space: since fluid intake and diuresis were comparable in the three treatment groups, any beneficial, selepressinrelated effect on tissue edema must have resulted from less pronounced vascular barrier "porosity" (8).…”
mentioning
confidence: 93%
“…What are possible clinical implications of the study by He et al (17)? The beneficial effects of the selepressin treatment were particularly pronounced in the early intervention arm, and selepressin was not combined with the clinical standard norepinephrine.…”
mentioning
confidence: 98%
See 1 more Smart Citation